Identity Formation and Developing Meaningful Social Relationships: The Role of the Polish Catholic Community for Polish Young People Migrating to Sweden - Shmulyar Gréen, Oksana; Melander, Charlotte; Höjer, Ingrid (Frontiers in Sociology, 2021)
This article draws from a broader research project Transnational childhoods, illuminating the agency and experiences of children and young people migrating from Poland and Romania to Sweden under the age of 18. Focusing on young people born in Poland and having social relationships post-migration as central theoretical component, the article explores the role that the Polish Catholic community in Sweden plays in the lives of young Polish migrants. It does so by grounding the analysis on 23 qualitative interviews, combined with network maps and life-lines, produced by the young Polish participants. The study identifies three important dimensions in the role of the Polish Catholic community. These are comprised of the community's role for young Poles' spiritual development and religious identity, for building new friendships and making sense of common migration and religious experiences, and guidance by specifically Polish Catholic priests in the young migrants' family relationships and in future life projects. The article concludes that while practicing religion and building significant social relationships within the Polish congregations the young migrants shape feelings of belonging and inclusion, however primarily within the limits of their own ethnic community. Further research is needed on the wider implications of primarily mono-ethnic relational practices for the young Poles' lives within the increasingly ethnically heterogeneous Swedish society.